2009
DOI: 10.2174/156802609789007363
|View full text |Cite
|
Sign up to set email alerts
|

Successful Structure-Based Design of Recent p38 MAP Kinase Inhibitors

Abstract: Inflammation is a complex immune response to cellular and tissue damage caused by physical, chemical, immunological, or microbial stimuli [1]. Prior to the successful launch of the anti-cytokine biologics [2-4], therapeutic approaches for the treatment of chronic inflammatory diseases such as rheumatoid arthritis and inflammatory bowel disease were associated with severe side effects. Although biological agents have revolutionized the treatment of inflammatory disorders, the high costs and inconvenient dosing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 72 publications
(183 reference statements)
0
27
0
Order By: Relevance
“…The α and β isoforms share a gatekeeper Threonine residue at position 106 (Thr 106) in both human and murine isoforms 4. This gatekeeper guards a hydrophobic (back)pocket(I) probed by the classic pyridinylimidazole inhibitors discovered to have anti-inflammatory activity through inhibition of this pathway almost two decades ago 5. The terms in parenthesis apply to the nomenclature adopted to describe the 5 sub-regions of ATP-binding site used in the design of ATP-competitive inhibitors 5.…”
Section: Structural Determinants Of P38 Utilized By Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The α and β isoforms share a gatekeeper Threonine residue at position 106 (Thr 106) in both human and murine isoforms 4. This gatekeeper guards a hydrophobic (back)pocket(I) probed by the classic pyridinylimidazole inhibitors discovered to have anti-inflammatory activity through inhibition of this pathway almost two decades ago 5. The terms in parenthesis apply to the nomenclature adopted to describe the 5 sub-regions of ATP-binding site used in the design of ATP-competitive inhibitors 5.…”
Section: Structural Determinants Of P38 Utilized By Inhibitorsmentioning
confidence: 99%
“…This gatekeeper guards a hydrophobic (back)pocket(I) probed by the classic pyridinylimidazole inhibitors discovered to have anti-inflammatory activity through inhibition of this pathway almost two decades ago 5. The terms in parenthesis apply to the nomenclature adopted to describe the 5 sub-regions of ATP-binding site used in the design of ATP-competitive inhibitors 5. A number of other scaffolds that also rely on this gatekeeper have also been developed (see58 for reviews).…”
Section: Structural Determinants Of P38 Utilized By Inhibitorsmentioning
confidence: 99%
“…These results suggested that MEK blockade could be useful for attenuating proinflammatory cytokine synthesis as well as for suppressing osteoclast-mediated bone erosions in inflammatory arthritis. However, the “cross-talk” that is known to occur between the JAK/STAT and MEK/ERK pathway [28, 76] likely also creates an added layer of complexity for regulating osteoclast function in inflammatory arthritis since the JAK/STAT pathway has also been considered as a suitable target pathway for the suppression of inflammatory disorders [26]. In that regard, Kwak et al [77] showed that AG-490, an inhibitor of Jak2/Jak3 activity, actually induced osteoclast survival by activating both the MEK/ERK and PI3K/PTEN/Akt cell survival pathway.…”
Section: Mek/erk 1/2mentioning
confidence: 99%
“…A previously published compilation of review articles highlighted the recent advances in the identification of novel targets and cellular processes in RA, which included non-IL-1, non-TNF- α and non-IL-6 proinflammatory cytokines, chemokines, adhesion molecules, vascular endothelial growth factor and insulin-like growth factor-1, matrix metalloproteinases (MMPs), complement and pro- and antiapoptosis molecules [25] as well as the Janus kinase/Signal Transducers and Activators of Transcription (JAK/STAT) pathway whereby the Jak3 inhibitor, CP690550 is the first small molecule inhibitor (SMI) to reach phase III clinical trials status [26], Mitogen-Activated Protein Kinase (MAPK) pathway [27, 28], and the IL-6/IL-6 receptor/gp130 complex [29, 30], all of which are applicable to additional basic and clinical studies wherein their future use in the medical intervention of adult and childhood RA and other inflammatory arthopathies may be further assessed. …”
Section: Introductionmentioning
confidence: 99%
“…[8] Various well-known ATP-competitive MAPK inhibitors have since been developed which are derived from the prototype inhibitors SK&F 86002 and SB 203580 (Figure 1). [10][11][12] Various potent and selective p38a inhibitors are currently in phase II clinical studies for rheumatoid arthritis, psoriasis, inflammatory bowel diseases, neuropathic pain, cancer, depression, and cardiovascular diseases. [13] With respect to the pyridinylimidazoles, it was revealed that 2-sulfanylimidazoles offer advantages over SB 203580, such as fewer cytochrome P450 (CYP450) interactions and improved kinetic properties.…”
Section: Introductionmentioning
confidence: 99%